(Z)-4-[2-(3,4-Difluorophenyl)hydrazono]-3-methyl-1H-pyrazol-5(4H)-one - Billava Jayappa Mohan (Molbank, 2018)
The title compound (Z)-4-[2-(3,4-difluorophenyl)hydrazono]-3-methyl-1H-pyrazol-5(4H)-one 4 was synthesized by the reaction of ethyl 2-[2-(3,4-difluorophenyl)hydrazono]-3-oxobutanoate 3 with hydrazine hydrate. The diazotization of 3,4-difluoroaniline, followed by the treatment with ethyl acetoacetate, afforded intermediate 3. The synthesized compound 4 was characterized by FTIR, 1H-NMR, 13C-NMR and LCMS, and it showed synergistic anti-inflammatory, antiproliferative and antibacterial activities.